The development of acoustics in the religious architecture of Cairo from the Arab conquest through the Ottoman period 640-1914 - Hussein, Ahmad (AUC Knowledge Fountain, 2016)
It is strongly believed that the scholarship in the field of Islamic art and architecture ‎still has many important under-researched areas, behind its visual aspects, that need to ‎be explored and analyzed. Archaeoacoustics, which is scientifically known as "The ‎archaeology of sound," is considered one of the significant disciplines in the field of ‎acoustics due to its role in revealing priceless information about different ‎archaeological sites and historic buildings around the world from the acoustic ‎perspective. Unfortunately, the archaeoacoustic studies of historic Islamic religious ‎buildings, especially in Cairo, are relatively neglected. Accordingly, this study aims in ‎the first place at analyzing the archaeoacoustic aspects and development of major ‎Cairene religious buildings, from the time of the Arab conquest through the Ottoman ‎period, in their relation to modern acoustics. Such analysis is believed to contribute ‎effectively in partially reconstructing the soundscape of the examined historic ‎buildings with regards to answering the following question: to what extent had the ‎architect, throughout the different the different periods of the Islamic history of ‎Cairo, been acquainted with the architectural acoustics principles? And how did that ‎knowledge affect the architectural designs of his religious buildings? ‎